2013
DOI: 10.1002/pola.26601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of hydroxy‐bisphosphonate micrometer‐sized particles by dispersion polymerization of a new styrylbisphosphonate monomer

Abstract: Bisphosphonates (BPs) are nonhydrolyzable pyrophosphate (P‐O‐P) analogs possessing two phosphonate groups linked to a single carbon (P‐C‐P). The hydroxy‐bisphosphonates (hydroxyBPs) are obtained when the hydroxy group is also linked to this bridging carbon. Their ability to form bidentate or tridentate chelates with calcium ions results in a high affinity to hydroxyapatite (HAP) in dentin, enamel and bones. In this study, we designed and prepared crosslinked poly(styrylbisphosphonate) (PStBP) micrometer‐sized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In our laboratory, a number of new BP vinylic monomers were synthesized, some via direct C–P bonds, in the absence of an amide bond, each monomer has different properties and can be used in numerous fields (Fig. ) . This synthesis of various vinylic monomers was the outcome of an ongoing research in the field of biodegradable polymers and molecules …”
Section: Introductionmentioning
confidence: 81%
“…In our laboratory, a number of new BP vinylic monomers were synthesized, some via direct C–P bonds, in the absence of an amide bond, each monomer has different properties and can be used in numerous fields (Fig. ) . This synthesis of various vinylic monomers was the outcome of an ongoing research in the field of biodegradable polymers and molecules …”
Section: Introductionmentioning
confidence: 81%
“…In our previous studies, we reported on the synthesis of new bisphosphonate vinylic monomers: styryl BP and PEG methacrylate BP (MA‐PEG‐BP) and formation of micrometer‐sized particles prepared from these monomer . This manuscript describes the synthesis and characterization of NIR fluorescent crosslinked BP nanoparticles for bone imaging and targeting.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Despite its remarkable value, only a few syntheses strategies have been developed for the preparation of phosphorylated or phosphonylated vinylbenzyls, and related molecules. [5][6][7][8]13,[15][16][17][18][19][20] The aforementioned compounds' syntheses were realized by the formation of the bond between phosphorus with benzyl carbon atoms via nucleophilic substitution adapting Michaelis-Arbuzov or Michaelis-Becker reaction (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Phosphonated polymers have been demonstrated strong adsorption to tooth enamel which could be used as a new type of restorative material or act as an effective adhesive between conventional polymeric restorative materials and the tooth. [5][6][7][8] Phosphoruscontaining polymers also improve the flame retardant properties of materials. [9][10][11] The phosphonated polymers have been used for metal separation or metal sorption from solutions.…”
Section: Introductionmentioning
confidence: 99%